ORTHOGRAPHIC, LEXICAL AND GRAMMATICALDIFFERENCES IN BRITISH AND AMERICAN NEWSPAPERS - Madoyan, Narine (Armenian Folia Anglistika, 2024)
The current article explores the nuanced distinctions between British and American English, particularly focusing on their systematic peculiarities as observed in online newspapers. It discusses how the evolution of newspapers has significantly influenced their style and language over time.Orthographic, lexical, and grammatical variations are well-known features of both British and American English. This article highlights the primary systematic differences between the two. While historically there has been a clear demarcation between British and American English, recent research suggests that this boundary is becoming increasingly blurred.Many prominent American newspapers are now adopting orthographic, lexical, and grammatical conventions traditionally associated with British English. Similarly, renowned British newspapers are showing a tendency to embrace simplified spelling and vocabulary more typical of American English. This mutual influence indicates that neither variety is entirely isolated or static; rather, there is a noticeable convergence between them, which is becoming more apparent over time.
Keywords: British English; American English; newspaper style; headlines; orthography; grammar; vocabulary; convergence